2012
DOI: 10.1371/journal.pone.0052246
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Modular Scale-Down Device for Regenerative Medicine Process Development

Abstract: The capacity of milli and micro litre bioreactors to accelerate process development has been successfully demonstrated in traditional biotechnology. However, for regenerative medicine present smaller scale culture methods cannot cope with the wide range of processing variables that need to be evaluated. Existing microfabricated culture devices, which could test different culture variables with a minimum amount of resources (e.g. expensive culture medium), are typically not designed with process development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 50 publications
(58 reference statements)
1
46
1
Order By: Relevance
“…Reichen et al [68] have shown that the quantification of cell specific attributes can be measured in high throughput microfluidic devices, however the behaviour of cells on flat surfaces may not be necessarily predictive of that on surfaces possessing curvature such as for instance on microcarriers. Shear stress is a factor that can be encountered in multiple units of operation from impeller shear to acute capillary shear during flow through orifices and capillaries.…”
Section: Making Use Of Scale-down Autologous Bioprocess Pipelinesmentioning
confidence: 99%
“…Reichen et al [68] have shown that the quantification of cell specific attributes can be measured in high throughput microfluidic devices, however the behaviour of cells on flat surfaces may not be necessarily predictive of that on surfaces possessing curvature such as for instance on microcarriers. Shear stress is a factor that can be encountered in multiple units of operation from impeller shear to acute capillary shear during flow through orifices and capillaries.…”
Section: Making Use Of Scale-down Autologous Bioprocess Pipelinesmentioning
confidence: 99%
“…32 Briefly, reusable components and the PDMS chip were sterilised separately by autoclave before assembly in a biological safety cabinet. Culture surface coating and cell seeding were carried out by pipette before placing the system in an incubator during cell attachment.…”
Section: Human Embryonic Stem Cell Cultivationmentioning
confidence: 99%
“…2 and has been described previously. 32 It consisted of a disposable PDMS microfluidic layer (containing a culture chamber volume of 25 µL and microfluidic channels) placed on a microscope-format TC-PS slide. Polycarbonate frames and interconnects provided packaging, sealing and connection with external pumping systems.…”
Section: Microfabricated Device For Adherent Stem Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Micronit, microLIQUID) or are mainly meant for PDMS cell culture devices. [250][251][252] To overcome these issues, a platform was developed in which entirely closed microfluidic systems made from gas-impermeable materials can be used for cell culture under varying physiological conditions (Fig. 3.1).…”
Section: The New Gradient Wavementioning
confidence: 99%